Thinking with the church: essays in historical theology - Gerrish, B. A. (William B. Eerdmans Pub. Co, 2010)
Introduction: "Thinking with the church" -- Revelation -- Revelation and the religion of reason -- Errors and insights in the understanding of Revelation -- Faith and morals -- Idolatrous faith : Fichte's atheism controversy -- Toward a moral theology : Forberg and practical belief -- Feuerbach's religious illusion -- The Calvinist tradition -- The place of Calvin in Christian theology -- Charles Hodge and the Europeans -- Constructing tradition : Calvin, Schleiermacher, and Hodge -- Atonement -- Charles Hodge on the death of Christ -- John Williamson Nevin on the life of Christ -- The Eucharist and the grace of Christ -- The Reformation and the Eucharist -- The grace of Christ